1998
DOI: 10.1161/01.res.82.4.438
|View full text |Cite
|
Sign up to set email alerts
|

Fas (CD95/Apo-1)–Mediated Damage to Ventricular Myocytes Induced by Cytotoxic T Lymphocytes From Perforin-Deficient Mice

Abstract: —Cytotoxic T lymphocytes (CTLs) that infiltrate the heart are important immune effectors implicated in heart transplant rejection, myocarditis, and other cardiomyopathies. To investigate the mechanism(s) underlying CTL damage to the myocardium through activation of the Fas receptor (Fas/CD95/Apo-1) by the Fas ligand, we explored the interaction between peritoneal exudate CTLs (PELs), derived from perforin gene–knockout (P−/−) mice, and murine ventricular myocytes. Fas expression on isolated ventricular myocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 42 publications
7
72
0
Order By: Relevance
“…Thus, reduced sensitivity to CD95-mediated apoptosis signals can conceivably lead to escape of virusinfected cells from immune surveillance. [17][18][19][20][21][22] Here we have found elevated levels of HGF and EGF in HBVinfected individuals and show that these growth factors stimulate survival signaling in primary human hepatocytes. Our findings support the notion that survival programs induced by EGF/HGF signaling may contribute to an apoptosis resistant phenotype in hepatocytes in the infected liver, thus contributing to immune escape and persistence of the viral infection.…”
mentioning
confidence: 53%
“…Thus, reduced sensitivity to CD95-mediated apoptosis signals can conceivably lead to escape of virusinfected cells from immune surveillance. [17][18][19][20][21][22] Here we have found elevated levels of HGF and EGF in HBVinfected individuals and show that these growth factors stimulate survival signaling in primary human hepatocytes. Our findings support the notion that survival programs induced by EGF/HGF signaling may contribute to an apoptosis resistant phenotype in hepatocytes in the infected liver, thus contributing to immune escape and persistence of the viral infection.…”
mentioning
confidence: 53%
“…In contrast, an in-vitro study has reported that the inflammatory cytokine or Fas /Fas ligand mediated apoptosis would change the ionic currents of myocyte. 27 Our present study is the first in-vivo report that documented the electrical remodeling in a model of CHF include by inflammatory process. The role of the inflammation in the ventricular electrical remodeling should be investigated in the future studies.…”
Section: The Electrical Remodering In Congestive Heartmentioning
confidence: 67%
“…Rather than reinforcing their positive contribution to inotropy, the overwhelming majority of studies that have examined the consequence of activating IP 3 Rs in ventricular myocytes have concluded that the predominant effect is to stimulate arrhythmias [62,143]. Indeed, IP 3 R activity has been suggested to underlie ventricular arrhythmias resulting from hormonal stimulation [143], reperfusion [144,145], engagement of cytotoxic T-lymphocytes [146] and FAS receptor activation [147]. These data suggest that Ca 2+ flux through the relatively few IP 3 Rs in ventricular myocytes is perhaps more dangerous than beneficial, similar to the situation discussed above for atrial cells.…”
Section: Ip 3 Signaling In Ventricular Myocytesmentioning
confidence: 99%